Effects of High Toxic Boron Concentration on Protein Profiles in Roots of Two Citrus Species Differing in Boron-Tolerance Revealed by a 2-DE Based MS Approach - Sang, Wen; Huang, Zeng-Rong; Yang, Lin-Tong; Guo, Peng; Ye, Xin; Chen, Li-Song (Frontiers in Plant Science, 2017)
Citrus are sensitive to boron (B)-toxicity. In China, B-toxicity occurs in some citrus orchards. So far, limited data are available on B-toxicity-responsive proteins in higher plants. Thirteen -week-old seedlings of ‘Sour pummelo’ (Citrus grandis) and ‘Xuegan’ (Citrus sinensis) was fertilized every other day until dripping with nutrient solution containing 10 μM (control) or 400 μM (B-toxicity) H3BO3 for 15 weeks. The typical B-toxic symptom only occurred in 400 μM B-treated C. grandis leaves, and that B-toxicity decreased root dry weight more in C. grandis seedlings than in C. sinensis ones, demonstrating that C. sinensis was more tolerant to B-toxicity than C. grandis. Using a 2-dimensional electrophoresis (2-DE) based MS approach, we identified 27 up- and four down-accumulated, and 28 up- and 13 down-accumulated proteins in B-toxic C. sinensis and C. grandis roots, respectively. Most of these proteins were isolated only from B-toxic C. sinensis or C. grandis roots, only nine B-toxicity-responsive proteins were shared by the two citrus species. Great differences existed in B-toxicity-induced alterations of protein profiles between C. sinensis and C. grandis roots. More proteins related to detoxification were up-accumulated in B-toxic C. grandis roots than in B-toxic C. sinensis roots to meet the increased requirement for the detoxification of the more reactive oxygen species and other toxic compounds such as aldehydes in the former. For the first time, we demonstrated that the active methyl cycle was induced and repressed in B-toxic C. sinensis and C. grandis roots, respectively, and that C. sinensis roots had a better capacity to keep cell wall and cytoskeleton integrity than C. grandis roots in response to B-toxicity, which might be responsible for the higher B-tolerance of C. sinensis. In addition, proteins involved in nucleic acid metabolism, biological regulation and signal transduction might play a role in the higher B-tolerance of C. sinensis.